Characterization of Hydroxyapatite of Chicken Eggshells Composite with Gelatin as Methylene Blue Absorbent - Nurfadillah; Ramadani, Kurnia; Firnanelty; Chadijah, Sitti; Aisyah, Aisyah; Ilyas, Asriani; Nur, Arfiani; Adawiah, Syarifah Rabiatul; Andriani, Titik (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2023)
Chicken egg shells contain an inorganic element (CaCO3) which has potency to be a source of calcium hydroxide (Ca(OH)2) which is then reacted with diammonium hydrogen phosphate ((NH4)2HPO4) as a phosphate precursor for hydroxyapatite synthesis. This study aims to determine the characterization of hydroxyapatite from eggshells and determine the absorbability of hydroxyapatite-gelatin composites against methylene blue. Synthesis of hydroxyapatite used precipitation method. The calcination results obtained calcium hydroxide (Ca(OH)2) content in the shell of 68.3%. Analysis of hydroxyapatite with Fourier Tranform Infra-Red (FT-IR) there was a wavenumber of 3434 cm-1 perform hydroxyl groups (-OH-), 1421 cm-1 carbonate groups (-CO3-2) and 1035 cm-1, 604 cm-1, 471 cm-1 phosphate groups (-PO4-2), and analysis by x-ray diffraction revealed that pure hydroxyapatite crystals had formed at an angle of 2Ɵ = 34,08 with crystallinity of 100%. The peaks that appear on the XRD diffractogram are adjusted to the Joint Committee on Power Diffraction Standards (JCPDS) No. 09-0432. The synthesis of HAp-gelatin composites obtained typical groups such as, amine groups from gelatin and phosphate groups and carbonates from Hap. The results of methylene blue absorption using hydroxyapatite-gelatin composites have obtained optimum conditions at a ratio of 2: 4 for 240 minutes with an efficiency of 63%. Based on these data, it reveals that the longer the time given, the greater the methylene blue absorbed